A focus group study of women's views and experiences of maternity care as delivered collaboratively by midwives and health visitors in England - Maria Raisa Jessica V. Aquino; Ellinor K. Olander; Rosamund M. Bryar (BMC, 2018)
Abstract Background Research suggests that collaboratively delivered maternity care can positively impact health outcomes. However, women's perspectives on models of care involving interprofessional collaboration between midwives and health visitors are not well understood. Accounts of women's maternity care experiences are key to improving maternity services. This study considered women's views and experiences of maternity care as collaboratively provided by midwives and health visitors in England. Methods A qualitative focus group study with an exercise exploring women's ideal maternity care pathway was conducted. Three focus groups were conducted in London, England between June and August 2017 with women who had had a child within 18 months prior to the study. The participants (n = 12) were recruited from two Children's Centres in London, England. Data were analysed using thematic analysis. Results Four themes were identified: 'Women's experiences of maternity care from midwives and health visitors', 'Midwife-health visitor communication', 'Midwife-health visitor collaboration for tailored care', and 'Women's ideal maternity care pathway'. Regarding women's experiences of interprofessional collaboration between midwives and health visitors, this was rarely encountered, but welcomed by women. Women's observations of limited tailored care and co-ordination led to several suggestions to improve maternity care, including secure, shared medical recordkeeping systems, clarity on midwives' and health visitors' roles, as well as increased communication. Conclusions Maternity care that is collaboratively delivered by midwives and health visitors, from the perspectives of the women in this study, is not routinely provided. However, women recognise the potential benefits of midwife-health visitor collaboration. Future research should explore service configurations that support integrated maternity care pathways, and evaluate the impact of midwife-health visitor collaboration on health and service outcomes.